Tuberculosis as a Global Health Problem: A Review of the Literature on Its Prevention and Development in Indonesia - Fitriana, Fitriana; Rifki, Moh.; Alkaff, Sy. Rugaiyah; Sudirman, Sudirman; Yani, Ahmad (Devotion : Journal of Research and Community Service, 2025)
Indonesia is the country with the second highest burden of Tuberculosis (TB) in the world. It is estimated that there are 845,000 new cases of TB every year with a death rate of 98,000 cases or equivalent to 11 deaths/hour. Tuberculosis control is directed to accelerate TB elimination by 2030. The transmission and development of TB disease is increasingly widespread because it is influenced by social factors such as poverty, urbanization, less active lifestyles, tobacco use, and alcohol. This research uses the literature review method and obtained 7 relevant journals. The results of this study show that the implementation of TB control programs in several health centers still faces various obstacles, especially in terms of funding, limited human resources, lack of SOPs, and not optimal technical implementation such as the discovery of active cases and the involvement of cadres.